PLAN PARCIAL NARANJAL - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2009)
Abstract. The process of increasing metropolización of Medellín, product of its conurbación with the other Municipalities of the Valley of Bores, has given origin to the structuring of new social and economic forms that are characterized, of a side, by increasing levels of agglomeration, concentration of activities, functions and relations; and of another side, by a high degree of concentration of the population. Resumen. El proceso de metropolización creciente de Medellín, producto de su conurbación con los demás Municipios del Valle de Aburra, ha dado origen a la estructuración de formas sociales y económicas nuevas que se caracterizan, de un lado, por crecientes niveles de aglomeración, por concentración de actividades, funciones y relaciones; y de otro lado, por un elevado grado de concentración de la población